Variation in body mass dynamics among sites in Black Brant Branta bernicla nigricans supports adaptivity of mass loss during moult. (8th June 2013) - Fondell, Thomas F.; Flint, Paul L.; Schmutz, Joel A.; Schamber, Jason L.; Nicolai, Christopher A.; Bolton, Mark
<x xml:space="preserve">Abstract</x> Birds employ varying strategies to accommodate the energetic demands of moult, one important example being changes in body mass. To understand better their physiological and ecological significance, we tested three hypotheses concerning body mass dynamics during moult. We studied Black Brant in 2006 and 2007 moulting at three sites in Alaska which varied in food availability, breeding status and whether geese undertook a moult migration. First we predicted that if mass loss during moult were simply the result of inadequate food resources then mass loss would be highest where food was least available. Secondly, we predicted that if mass loss during moult were adaptive, allowing birds to reduce activity during moult, then birds would gain mass prior to moult where feeding conditions allowed and mass loss would be positively related to mass at moult initiation. Thirdly, we predicted that if mass loss during moult were adaptive, allowing birds to regain flight sooner, then across sites and groups, mass at the end of the flightless period would converge on a theoretical optimum, i.e. the mass that permits the earliest possible return to flight. Mass loss was greatest where food was most available and thus our results did not support the prediction that mass loss resulted from inadequate food availability. Mass at moult initiation was positively related to both food availability and mass loss. In addition, among sites and years, variation in mass was high at moult initiation but greatly reduced at the end of the flightless period, appearing to converge. Thus, our results supported multiple predictions that mass loss during moult was adaptive and that the optimal moulting strategy was to gain mass prior to the flightless period, then through behavioural modifications use these body reserves to reduce activity and in so doing also reduce wing loading. Geese that undertook a moult migration initiated moult at the highest mass, indicating that they were more than able to compensate for the energetic cost of the migration. Because Brant frequently change moult sites between years in relation to breeding success, the site‐specific variation in body mass dynamics we observed suggests individual plasticity in moult body mass dynamics.